Embryonic and larval development is conditioned by water temperature and maternal origin of eggs in the sea urchin Arbacia dufresnii (Echinodermata: Echinoidea) - Fernandez, Jimena Pía (2021)
Introduction: Embryonic and larval development in sea urchins is highly dependent on maternal nutritionalstatus and on the environmental conditions of the seawater. Objective: To compare the development of Arbaciadufresnii in two different water temperatures and in progeny with varying maternal origins. Methods: Weinduced A. dufresnii females and males from Nuevo Gulf to spawn, collected the eggs of each female individually(progeny), separated them into two seawater temperatures (12 and 17 °C), and fertilized them. We recordedthe percentage of fertilized eggs and embryos per developmental stage according to time, temperature andprogeny. We measured larval growth by total length (TL) and midline body length (M) according to time postfecundation (DPF), temperature, and progeny. Results: Temperature did not affect fertilization, but embryodevelopment was faster and more synchronized in the high temperature treatment. The generalized linear modelsindicate that embryo development depends on a quadruple interaction between the embryonic stage, time (h),seawater temperature and progeny. Larval growth was faster, producing larger larvae at the highest temperature.Larval growth depends on a triple interaction between time (DPF), seawater temperature and progeny.Conclusions: We found a temperature and progeny impact during embryonic and larval development and, inboth cases, these factors generate a synergistic effect on developmental timing and larval size. This probablyprovides a survival advantage as a more rapid speed of development implies a decrease in the time spent in thewater column, where the sea urchins are vulnerable to biotic and abiotic stressors.